Survey of conditions for artificial aurora experiments at EISCAT Tromsø using dynasonde data - Tsuda, T. T.; Rietveld, Michael T; Kosch, Michael J.; Oyama, S; Hosokawa, K.; Nozawa, Satonori; Kawabata, T; Mizuno, A; Ogawa, Y (Earth, Planets and Space, 2018)
Source at https://doi.org/10.1186/s40623-018-0805-9 . Licensed CC BY-NC-ND 4.0. We report a brief survey on conditions for artificial aurora optical experiments in F region heating with O-mode at the EISCAT Tromsø site using dynasonde data from 2000 to 2017. The results obtained in our survey indicate the following: The possible conditions for conducting artificial aurora experiments are concentrated in twilight hours in both evening and morning, compared with late-night hours; the possible conditions appear in fall, winter, and spring, while there is no chance in summer, and the month-to-month variation among fall, winter, and spring is not clear. The year-to-year variation is well correlated with the solar cycle, and experiments during the solar minimum would be almost hopeless. These findings are useful for planning future artificial aurora optical experiments.